Fetal Reduction From Twin to Singleton Gestation: A Meta-analysis. Issue 1 (22nd March 2023) - Bardin, R.; Gupta, M.; Greenberg, G.; Nandrajog, A.; Tenenbaum-Gavish, K.; Gupta, N.; Perlman, S.; Shmueli, A.; Hadar, E.
Abstract : ( Int J Gynaecol Obstet . 2022;158:260–269) Fetal reduction may be requested by parents in a multiparous pregnancy with normally developing fetuses in favor of supporting maternal medical conditions, psychological factors, poorly resourced socioeconomic status, or to improve projected pregnancy outcome. This is in contrast to selective termination where there is an abnormal fetus in a multiparous pregnancy. Twin pregnancies carry 2 to 3.5 times increased risk of maternal hypertensive and hyperglycemic complications, and 2 to 3 times increased risk of perinatal and infant mortality. Approximately 50% of twin pregnancies result in preterm birth (PTB), and further early PTB occurs in 14%. The benefits and drawbacks of multifetal reduction in triplets and quadruplets has been studied, but maternal, perinatal, and neonatal results for twins are inconsistent. This meta-analysis helps to clarify issues around fetal reduction compared to ongoing twin pregnancies.